Influence of fibre architecture on the tensile, compressive and flexural behaviour of 3D woven composites. (February 2015) - Dai, S.; Cunningham, P.R.; Marshall, S.; Silva, C.
Abstract: This paper presents a comprehensive study on the tensile, compressive, and flexural performance of six types of 3D woven carbon-fibre/epoxy composites which were manufactured using a traditional narrow fabric weaving loom and resin transfer moulding. Four orthogonal and two angle-interlock weaves were tested with the primary loading direction parallel to the warp direction. The mechanical performance was found to be affected by the distribution of resin rich regions and the waviness of the load-carrying fibres, which were determined by the fibre architectures. The binding points within the resin rich regions were found to be the damage initiation sites in all weave types under all loading conditions, which were confirmed with both visual observation and digital image correlation strain maps. Among all weave types, the angle interlock weave W-3 exhibited the highest properties under all loading conditions.